Investigating the Balance between Th17/Treg Cells in Rheumatoid Arthritis and its Association with Disease Activity - Taha, Hanan Aly; Hozayen, Walaa G.; Okasha, Ahmed Mohamed; Ahmed, Amr E.; Shata, Manar Ali A.; Abdel-Naem, Emad A.; Maher, Sheren Esam (Journal of Child Science, 2019)
Rheumatoid arthritis (RA) is a systemic autoimmune disorder characterized by articular inflammation and joint destruction. The mechanism of RA pathogenesis is not fully understood, but humoral and cellular immunity are known to be involved. CD4+ T lymphocytes and cytokines released by these cells are suggested to initiate inflammation in RA. This study aimed to assess T helper 17 (Th17)/regulatory T (Treg) cell ratio and its correlation with disease activity in adult and juvenile RA. This study included 80 patients, with RA, including 40 adults (mean age: 36.4 ± 11.1 years and 40 juveniles mean age: 12.7 ± 2.2 years), and 80 healthy controls. For all patients and control subjects, patient and disease characteristics; laboratory tests for complete blood count, erythrocyte sedimentation rate, C-reactive protein (CRP), rheumatoid factor, anti-cyclic citrullinated peptide (anti-CCP), anti-nuclear antibodies (ANA), and flow cytometry to determine the numbers of Th17 and Treg cells. There was a statistically significant increase in the Th17/Treg ratio in patients with active disease compared with those with inactive disease for both adult and juvenile RA compared with controls. However, a similar significant difference was not observed between those with inactive adult and juvenile RA and controls. There were significant positive correlations between the Th17/Treg ratio and disease activity score 28 (DAS28), CRP, anti-CCP, and ANA in active adult and juvenile RA. The Th17/Treg ratio was increased in active form of adult and juvenile RA compared with inactive RA and control, indicating the Th17/Treg ratio as a potentially useful marker of disease activity.
Keywords: Th17 cell; regulatory T cell; rheumatoid arthritis; disease activity